2013
DOI: 10.1111/petr.12092
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation with a reduced‐intensity conditioning regimen in pediatric patients withGriscelli syndrome type 2

Abstract: Partial albinism with variable immunodeficiency are the two major characteristics of Griscelli syndrome type 2 (GS-2). This syndrome is usually associated with a high mortality rate and commonly results in early childhood death. Patients suffer from different infections and experience crisis of HLH. HSCT remains the sole curative treatment for GS-2. We prospectively analyzed the outcomes of transplantation with RIC regimen in five patients. The median age at transplantation was 21.6 months (range: 12-30). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is the only treatment modality offering cure or long-term survival for a variety of pediatric and adult diseases, including hematologic malignancies, immunodeficiencies, hemoglobinopathies, and metabolic disorders [1,2]. An identical sibling is considered the optimal donor, as he or she is more likely to be matched with the recipient and use of an immunologically identical sibling is associated with better clinical outcome and reduced rates of transplant-related complications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is the only treatment modality offering cure or long-term survival for a variety of pediatric and adult diseases, including hematologic malignancies, immunodeficiencies, hemoglobinopathies, and metabolic disorders [1,2]. An identical sibling is considered the optimal donor, as he or she is more likely to be matched with the recipient and use of an immunologically identical sibling is associated with better clinical outcome and reduced rates of transplant-related complications [1].…”
Section: Introductionmentioning
confidence: 99%
“…Three patients were diagnosed with FHLH and 2 patients had Chediak–Higashi syndrome. Five other patients had GS‐II whose data with shorter follow‐up period were published in another article .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the rarity of primary HLH, few studies have reported the results of transplantation in these patients . There are published reports of patients including adults and pediatric patients diagnosed with HLH (primary and secondary) and treated with MAC and RIC regimens . So, it seems difficult to select a suitable conditioning regimen for pediatric patients with primary HLH.…”
Section: Discussionmentioning
confidence: 99%
“…PIDs are rare genetic diseases and most of them are lethal in childhood, mainly due to serious infections. Despite allogeneic HSCT being recognized as a curative approach in children suffering from various types of PIDs [27][28][29] and in spite of improved techniques a number of issues remain to be answered including the best conditioning regimen and the level of chimerism that would ensure cure. Introduction of RIC has offered many patients ineligible for MAC a chance for cure.…”
Section: Discussionmentioning
confidence: 99%